1994
DOI: 10.1111/j.1432-1033.1994.00981.x
|View full text |Cite
|
Sign up to set email alerts
|

Purification, Properties and Structural Aspects of a Thermoacidophilic α‐Amylase from Alicyclobacillus Acidocaldarius Atcc 27009

Abstract: The a-amylase from the thermoacidophilic eubacterium Alicyclobacillus (Bacillus) acidocaldarius strain ATCC 27009 was studied as an example of an acidophilic protein. The enzyme was purified from the culture fluid. On an SDS/polyacrylamide gel, the protein exhibited an apparent molecular mass of 160 kDa, which is approximately 15% higher than that predicted from the nucleotide sequence. The difference is due to the enzyme being a glycoprotein. Deglycosylation or synthesis of the enzyme in Escherichia coli gave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
48
0
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(51 citation statements)
references
References 61 publications
2
48
0
1
Order By: Relevance
“…Selective agar plates (pH 4), containing basal salts, 0.5% konjac glucomannan, and 1.5% agar (w/v), were prepared as described elsewhere (26). Mud and water samples from an acidic hot spring in Tengchong (Yunnan province, China) were spread on the selective agar plates at 100 l/plate; this was followed by incubation for 48 h at 60°C.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Selective agar plates (pH 4), containing basal salts, 0.5% konjac glucomannan, and 1.5% agar (w/v), were prepared as described elsewhere (26). Mud and water samples from an acidic hot spring in Tengchong (Yunnan province, China) were spread on the selective agar plates at 100 l/plate; this was followed by incubation for 48 h at 60°C.…”
Section: Methodsmentioning
confidence: 99%
“…The colonies thus obtained were replicated on selective agar plates and cultured. Mannanase-producing colonies were detected by flooding the plates with 0.1% (w/v) Congo Red solution (26,27). Strain Tc-12-31, which gave the largest clear lysis zone, was selected.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cleavage of the protein during the preparation is believed to be due to the action of an extracellular protease. 8 Dynamic light scattering experiments showed this sample represented a monomer of molecular weight 42 kDa in the temperature range þ 5 8C to þ 50 8C.…”
Section: Protein Expression and Purificationmentioning
confidence: 99%
“…This Gram-positive bacterium has a pH optimum of 3.6 and a temperature optimum of 57 8C. 5,6 Comparison of the core (ba) 8 -barrel domain of the secreted a-amylase (amylopullulanase) 7 from A. acidocaldarius with the available structures of homologous proteins from mesophilic organisms indicated that charged amino acid residues were often replaced with polar but uncharged ones in the thermoacidophile's protein, especially on the molecular surface. 8 This trend had not been identified in thermostable proteins, and so was believed to reflect the enzymes's acidostability.…”
Section: Introductionmentioning
confidence: 99%